The formation and development of political territory and borders in Ionia from the Archaic to the Hellenistic periods: A GIS analysis of regional space - Hill, David (Journal of Greek Archaeology, 2019)
The purpose of this article is to present a set of geopolitical maps of Ionia from the Archaic to the Hellenistic periods using a range of sources and by applying comparative models drawn from a number of Greek regions. The maps represent the first attempt to visualise geopolitical Ionia. The borders and territories of the Ionian poleis have been identified and drawn on two maps to represent the geopolitical situation at the time of polis formation in the 8th century BC, and again in the 2nd century BC during the Hellenistic period when considerable changes to the political landscape were made. The motivation behind creating a geopolitical map of Ionia that plots the territories and borders of the Ionian poleis is to open discussion. Ionian and regional research has traditionally been carried out on a polis by polis basis.